El cuidado del niño: Representaciones y experiencias de la madre adolescente de bajos recursos - Turiani, Mariana; Pamplona Tonete, Vera Lucia [UNESP]; Komura Hoga, Luiza Akiko; Chávez Alvarez, Rocío Elizabeth (My University, 2009)
Objective: To describe the representations and experiences of the adolescent mother related to the child care. Method: A qualitative method was carried out and eight adolescent mothers were interviewed. Their narratives were analyzed according to the Collective Subject Discourse systematic. Three central themes emerged from narratives: 1- The initial experiences; 2- The daily care; 3- The care practices. The incorporation of the maternal role represented the conquest of a dream, carried out with difficulties, but overcome with family and other social networks support. Actions directed to reinforce this sustentation are necessary, in order to promote the child care conditions and to diminish the adolescent mother's child morbidity and mortality rates. © 2009.
The care of the child: Representations and experiences of low income adolescent mother
Keywords: Child health; Family; Health education; Pregnancy in adolescence